"Dear International Guests and Friends of the Icelandic Horse": Experience, Meaning and Belonging at a Niche Sporting Event. Issue 4 (1st October 2016) - Helgadóttir, Guðrún; Dashper, Katherine
ABSTRACT: Landsmót hestamanna is the national championships for the Icelandic horse and a major festival for the special interest group addressed by the event organisers as "Friends of the Icelandic horse". As the designated country of origin for this particular equine breed, Iceland has a special place in the discursive practices of the communities involved with the Icelandic horse worldwide, while the Icelandic horse plays an important role in the tourism marketing of Iceland as a destination. Participant observation was conducted at the 2012 Landsmót in Reykjavík by two independent observers; one was an international visitor while the other was a native of Iceland. The data collected raise interesting questions about belonging to a niche market and attending associated events, the social construction of event experiences, about being an insider and an outsider, and how these positions are contingent and changeable across spatial and temporal boundaries within the flow of an event.